HUBUNGAN PENDAPATAN, ASUPAN MAKAN DENGAN STATUS KESEHATAN BALITA GIZI KURANG DI WILAYAH KERJA PUSKESMAS KALUMATA KOTA TERNATE - Nur M. Ali (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2018)
Nutritional problems in Indonesia and in developing countries in general are still dominated by Protein Energy Deficiency (KEP), Iron Anemia problems, Iodine Deficiency Disorders (IDD), Lack of Vitamin A (KVA) and obesity problems, especially in big cities . Indonesia has a dual nutritional problem, which means that while the problem of malnutrition has not been fully addressed, new problems have emerged, namely over nutrition. The direct cause of malnutrition is unbalanced food intake and infectious diseases. Whereas for indirect causes including insufficient food supplies, inadequate parenting, inadequate sanitation / basic health services. This is due to poverty and poor family income. The aim of the study was to determine the relationship between income, food intake and health status of under-five children under five in the Work Area of ​​Kalumata Health Center, Ternate City. The research method used was an analytical survey with a cross sectional study design to see the relationship between income variables, food intake and health status of children under five using the chi-square statistical test. The number of samples in this study were 37 samples, sampling by consecutive sampling. The results of the test of energy intake statistics lacking with health status use chi-square values ​​with a value of P = 0.03 (<0.05). For less carbohydrate intake with health status often sick in toddlers obtained by the chi-square statistical test results with a value of P = 0.02 (<0.05). Statistical test results for variable fat intake less with health status are often sick with a P value of 0.64 (> 0.05). Protein intake of respondents with less categories and health status of children under five often sick obtained a chi-square value with a value of P = 0.02 (<0.05). Low family income with health status of children under five is often sick with a value of P = 0.06 (> 0.05). So that it can be concluded that there is a relationship between energy intake, carbohydrate, protein with balinese health status while the fat intake variable and parents' income are not related to underfive health status of malnourished children.